Análogos com o núcleo 3,4,5-trimetoxibenzoíla inspirados na piplartina : atividade tripanocida e citotóxica contra carcinoma bucal - Silva, Rayanne Hellen do Nascimento (2023)
Chagas disease is among the thirteen most neglected diseases in the world, despite being a well-reported and well-known pathology, it continues to be a socioeconomic problem in several Latin American countries. Another disease also considered a public health problem is cancer, such as head and neck cancer, the most common of which are located in the oral cavity and have a survival rate of just five years. Therefore, the search for new candidates for antiparasitic and antitumor drugs is essential. In the present work, a collection of twenty-three 3,4,5-trimethoxybenzoic acid derivatives were prepared via Fischer esterification, nucleophilic substitution using alkyl or aryl halide, Mitsunobu reaction and amidation with PyBOP. The structures of the products were characterized by infrared spectroscopy, ¹H and 13C NMR, and high-resolution mass spectrometry. Nine compounds are new to the literature, namely compounds 6, 9-11, 13-15, 22 and 23. The derivatives were evaluated for their inhibitory action against Trypanosoma cruzi and cytotoxic activity against tongue squamous cell carcinoma cells (SCC9). In the evaluation of trypanocidal activity, derivatives 15-18 and 20 were bioactive against the epimastigotes, trypomastigotes and amastigotes forms of T. cruzi. The N-iso-butyl-3,4,5-trimethoxybenzamide derivative (17) showed greater trypanocidal potency with IC50 = 2.21 μM and selectivity index (SI) = 298.6. The result shows that benzamides have a more promising antiparasitic action and that the presence of a bulky alkyl substituent enhances the trypanocidal action. In the molecular modeling study, a mechanism of action was suggested in which the most likely target of 17 in T. cruzi would be the enzyme histone deacetylase (HDAC). While the evaluation of cytotoxic activity was carried out using the MTT test, with compounds 1-8, 9, 13-17 and 19-23. Among the compounds tested, 4-methoxy-benzyl 3,4,5-trimethoxybenzoate (10) and the compound 4-methyl-benzyl 3,4,5-trimethoxybenzoate (11) presented IC50s of 46.21 and 68,69 μM, and demonstrated high selectivity, SI > 16 and 53, respectively. These derivatives also caused selective apoptosis in SCC9 cancer cells, suggesting that the presence of aromatic substituents with methyl or methoxy at the para position increases potency and selectivity. Molecular modeling of 10 suggested a multitarget mechanism of action for its antitumor activity with CRM1 as the main target receptor. Therefore, it can be concluded that some piplartin analogues have trypanocidal and antitumor action, however, more advanced studies are needed to better understand their possible mechanisms of action.